Influencing Factors for use of Skin Whitening Creams - Hafeez, Filza; Ahmad, Shakeel; Malik, Aisha; Niazi, Nuzha; Ishfaq, Rabia; Sheikh, Izza (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the frequency of influencing factors for the use of skin whitening creams. Study design: Descriptive, Cross-sectional study. Place and duration of study: Department of Dermatology, D.H.Q Hospital, Faisalabad Medical University, Faisalabad from 7th August 2018 to 6th February 2019. Methodology: A total of 420 patients presenting with complaints of acne, excessive hair growth, permanent redness, skin sensitivity, irritation and dark complexion after the use of skin whitening creams of age 15-50 years were included. Patients with diabetes mellitus, asthma, hypertension and tuberculosis, pregnancy and PCOS were excluded. The demographic data, socioeconomic status, education level and the major influencing factors for the use of commercially available skin whitening creams were inquired. Results: In this study, I have found the frequency of influencing factors for the use of skin whitening creams were as follows; television commercials in 108 (25.71%), print media/magazine in 61 (14.52%), friends in 131 (31.19%), spouse in 48 (11.43%), beauticians in 42 (10.0%) and self-desire in 30 (7.14%) patients. Conclusion: This study has shown that the friends and television commercials are main influencing factors for the use of skin whitening creams.